2019
DOI: 10.20944/preprints201904.0108.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacteriological Assessment and Antibiotics Susceptibility Profile of Bacteria Recovered from Pond Water, Fish Skin, and Gut in Ile-Ife, Osun State, Nigeria

Abstract: Fish currently provide 6.7% of all protein consumed by humans globally, nevertheless, aquaculture system has been linked to fish and environmental contamination and disease outbreak. This study aims to isolate, identify, and characterise, bacteria in fish and pond water as well as the antibiotic profile of detected Coliforms. The susceptibility of the isolates was tested using the Kirby-Bauer disc diffusion method on Mueller Hinton agar. A total of forty (40) isolates were isolated from the water samples of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Optimum pH directly stabilizes the physicochemical parameters of pond water, enhancing fish health and productivity, and the maintenance of a proper balance of the microbial ecology in pond water [21]. Fluctuations in pH have been reported to cause extreme stress in fish [6], since they are known to have an average blood pH of 7.4 [8]. It has been confirmed that the pH between 6.5 and 9 is most appropriate for maintenance and increased fish production [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Optimum pH directly stabilizes the physicochemical parameters of pond water, enhancing fish health and productivity, and the maintenance of a proper balance of the microbial ecology in pond water [21]. Fluctuations in pH have been reported to cause extreme stress in fish [6], since they are known to have an average blood pH of 7.4 [8]. It has been confirmed that the pH between 6.5 and 9 is most appropriate for maintenance and increased fish production [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Fishes are reared in different water culture media or confinement such as concrete, earthen or plastic ponds. Concrete and earthen ponds have been the widely used culture system for fish [6]. The contamination of these culture systems has been attributed to poor water quality, high stocking densities and the use of animal manure and contaminated feed [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fishes are reared in different water culture media or confinement such as concrete, earthen or plastic ponds. Concrete and earthen ponds have been the widely used culture system for fish [6]. Fishes reared in these environments are contaminated by both pathogenic and opportunistic microorganisms.…”
Section: Introductionmentioning
confidence: 99%